Особливості розвитку пубертату у хлопчиків із крипторхізмом - Султанова, Ш. Т. (Clinical Endocrinology and Endocrine Surgery, 2009)
The peculiarities and appropriateness of sexual development in uzbek-boys with cryptorchidism in Tashkent city and Tashkent oblast were studied in the work. The terms of initiation and succession of puberty were determined; the age dynamics of secondary sexual indicators were retraced. It was shown, that the development of secondary sexual indicators took place in consecutive order but with relative delay comparing with healthy boys for 1-2 years. However, there were noted reliable decreases of T, FCH, LH, from the beginning of pubertal age and as well as the decrease of the volume of testicles lowered by surgery means and size of the penis.